2017
DOI: 10.1039/c7ra10206b
|View full text |Cite
|
Sign up to set email alerts
|

Piezotronic-effect-enhanced Ag2S/ZnO photocatalyst for organic dye degradation

Abstract: Taking advantage of the piezotronic effect, enhanced photocatalytic performance of a Ag 2 S@ZnO hybrid photocatalyst was achieved under sonication. Decorating Ag 2 S ($1.4 eV bandgap) nanoparticles on ZnO ($3.3 eV bandgap) nanowire surfaces successfully extended the light response to the visible light range.The formation of type II band alignment at the Ag 2 S/ZnO heterointerface facilitated the separation of photoexcited electrons and holes, promoting utilization of photoexcited charge carriers in the photoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Figure b–d display the core‐level XPS spectra for Zn 2p, S 2p, and O 1s, respectively. The binding energies of Zn 2p 3/2 and Zn 2p 1/2 peaks at 1021.1 and 1044.2 eV (Figure b), respectively, which are assigned to the Zn 2+ in ZnS or ZnO . The peaks with binding energies of 160.8 and 161.9 eV are in well agreement with the peak positions for S 2p 3/2 and S 2p 1/2 , respectively, which belong to S 2− ions in ZnS crystal lattice .…”
Section: Resultssupporting
confidence: 72%
“…Figure b–d display the core‐level XPS spectra for Zn 2p, S 2p, and O 1s, respectively. The binding energies of Zn 2p 3/2 and Zn 2p 1/2 peaks at 1021.1 and 1044.2 eV (Figure b), respectively, which are assigned to the Zn 2+ in ZnS or ZnO . The peaks with binding energies of 160.8 and 161.9 eV are in well agreement with the peak positions for S 2p 3/2 and S 2p 1/2 , respectively, which belong to S 2− ions in ZnS crystal lattice .…”
Section: Resultssupporting
confidence: 72%
“…283 Compared to the pure piezoelectric semiconductor ZnO, hybrid semiconductors have better photocatalytic performance. 284,285 For example, when assembling TiO 2 nanodots on ZnO monocrystalline nanoplatelets, a piezoelectric potential can be induced in ZnO by applying a thermal stress to the piezoelectric ZnO nanoplatelets via cooling of the hybrid semiconductor from high temperature to room temperature at various cooling rates (Figure 62). 143,286 Because of the thermal expansion mismatch between these two materials, the lattice parameter of ZnO will change, thus tuning the band structure of the heterojunction and effectively enhancing the photocatalytic rate by enhancing the charge separation.…”
Section: Piezo-phototronic Effect In Electrochemical Processesmentioning
confidence: 99%
“…21 Zhang and coworkers reported that the photocatalytic performance of Ag 2 S@ZnO hybrid photocatalyst was enhanced by taking advantage of the piezotronic effect. 22 The fruitful results mentioned above indicate that one of the remaining challenges is the synthesis of high-performance photocatalysts by a facile and low-cost method. 1…”
Section: Introductionmentioning
confidence: 99%
“…21 Zhang and coworkers reported that the photocatalytic performance of Ag 2 S@ZnO hybrid photocatalyst was enhanced by taking advantage of the piezotronic effect. 22 The fruitful results mentioned above indicate that one of the remaining challenges is the synthesis of high-performance photocatalysts by a facile and low-cost method. 1 To the best of our knowledge, there has been limited research on the photocatalytic properties of cerium-zirconium mixed metal oxide composites (Ce x Zr y O 2 ) towards the photodegradation of MB.…”
Section: Introductionmentioning
confidence: 99%